Efektifitas Model Pembelajaran Problem Posing Ditinjau dari Kemampuan Literasi Matematis Siswa SMP pada Materi Aljabar - Prawidi Wisnu Subroto; Erine Yulianti Suhadi; Retno Julyana (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2019)
The purpose of this research was to find out the effectiveness of the problem posing learning models in terms of students' mathematical literacy abilities. The sample of this study was 31 students of class VII.6 PGRI 2 Junior High School in Ciledug. Purposive sampling technique was purposed in this research. Indicators of this study include: (1) elements of algebraic form; (2) algebraic form operations, which consist of: addition and subtraction, multiplication and division, rank, and the LCM and GCD algebraic concepts. This research uses a quantitative descriptive approach. The method used was a quasi experiment, with a one-group pretest-posttest design. The research instrument used was a mathematical literacy ability test. The results of this study were categorized into 4: high, medium, low and very low. Data analysis used pretest and posttest score for each indicator. Based on the results of paired sample t-test shows that there is a significant increase in each indicator. The calculation result of Gain value of 0.42 shows an increase in the medium category. This it can be concluded that the problem posing learning model is effective.